Satisfactory Level of Undergraduate Students with Academic Library: A Case study of Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka - Sivathaasan, N. (My University, 2013)
An academic library plays a vital role in order to contribute to its users in an efficient and effective manner to satisfy their thirst of knowledge as well as in our information society. They help to connect people with the ever changing world of information. This article investigates satisfactory level of undergraduates of Faculty of Management Studies & Commerce with the facilities offered by the main library, University of Jaffna. A self-developed questionnaire was used to measure the satisfaction on the statements relating to four dimensions with a sample of 202 students. Mean analysis reflects that students were relatively most satisfied with competence of library staff, followed by information sources, library environment and library general services. According to the regression analysis, library facilities have an impact on undergraduate satisfaction at the rate of 20.1 % which is significant at 0.05 levels.